1990
DOI: 10.1088/0954-3899/16/5/012
|View full text |Cite
|
Sign up to set email alerts
|

Time dispersion of muons in EAS

Abstract: Describes the results and conclusions from an experiment set up to measure the time spread of muons in extensive air showers (EAS) detected at the Haverah Park EAS detector array, UK. The pulse risetimes (T70) from 10% to 70% amplitude of the responses from 3*10 m2 muon detectors are studied, and the anomalous pulse structure is investigated. The mean T70 is studied as a function of shower size, zenith angle and core distance and its dependence on shower size is related to the elongation length of the EAS. Flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 15 publications
(5 reference statements)
0
12
0
Order By: Relevance
“…This may be due to the muon being produced at a large core (or angular) distance from the shower axis, such that the shower is not detected by the telescope. Alternatively, the muon may have triggered the Camera at a slightly different time, such as in advance of the rest of the shower, that the charge integrated over the 16 ns integration window is not sufficient to also contain the shower [16,17].…”
Section: Muon -Shower Event Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the muon being produced at a large core (or angular) distance from the shower axis, such that the shower is not detected by the telescope. Alternatively, the muon may have triggered the Camera at a slightly different time, such as in advance of the rest of the shower, that the charge integrated over the 16 ns integration window is not sufficient to also contain the shower [16,17].…”
Section: Muon -Shower Event Reconstructionmentioning
confidence: 99%
“…The LHC operates at p-p collision centre-of-mass energies of up to 14 TeV, corresponding to an initial CR proton energy of 1.0×10 17 eV. Therefore, within the sub-PeV sensitive range of IACT arrays, good agreement with LHCtuned simulations may be expected, as no extrapolations of hadronic interaction models in energy are required [31].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the Glashow-Iliopoulos-Maiani (GIM) mechanism [4], flavor changing neutral current (FCNC) induced semileptonic B decays are rare in the SM because these decays are forbidden at tree level and can proceed at the lowest order only via electroweak penguin and box diagrams [5,6]. Therefore, these decay processes provide sensitive probes to look into physics BSM [7]. They also play a significant role in providing a new framework to study the mixing between different generations of quarks by extracting the most accurate values of Cabibbo-Kobayashi-Maskawa (CKM) matrix elements which help us to test the charge-parity (CP) violation in the SM and to dig out the status of NP [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Local arrival time distributions display the internal structure of the shower disc (characterised by various time parameters), but they do not carry information about the shape (curvature) of the front. Nevertheless studies based on simulations of the EAS development [16,19] have shown that mass discrimination effects are just pronounced in observations of ∆τ 1 glob µ . For event-by-event observations with a fluctuating number of muons, the single relative arrival time distributions can be characterised by the mean values ∆τ mean , and by various quantiles ∆τ q , like the median ∆τ 0.50 , the first quartile ∆τ 0.25 and the third quartile ∆τ 0.75 .…”
Section: Introductionmentioning
confidence: 99%